2001
DOI: 10.2134/jeq2001.301171x
|View full text |Cite
|
Sign up to set email alerts
|

Using Zebra Mussels to Monitor Escherichia coli in Environmental Waters

Abstract: Use of the zebra mussel (Dreissena polymorpha) as an indicator of previously elevated bacteria concentrations in a watershed was examined. The ability of the zebra mussel to accumulate and purge Escherichia coli over several days was investigated in both laboratory and field experiments. In laboratory experiments, periodic enumeration of E. coli in mussels that had been exposed to a dilute solution of raw sewage demonstrated that (i) maximum concentrations of E. coli are reached within a few hours of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 12 publications
4
23
1
Order By: Relevance
“…Although in studies regarding enterobacterial removal from wastewater by D. polymorpha a 50% reduction was found after 24 h and almost 100% after 48 h (Selegean et al, 2001), our results showed a reduction of already 83.1% and 98.6% at T 4 and T 2 4, respectively, and almost 100% at T 48 . In the control samples, where zebra mussels were absent, the overtime decrease in E. coli colonies was slower, and can be due to the inactivation by toxic factors present in the wastewater.…”
Section: Discussioncontrasting
confidence: 89%
“…Although in studies regarding enterobacterial removal from wastewater by D. polymorpha a 50% reduction was found after 24 h and almost 100% after 48 h (Selegean et al, 2001), our results showed a reduction of already 83.1% and 98.6% at T 4 and T 2 4, respectively, and almost 100% at T 48 . In the control samples, where zebra mussels were absent, the overtime decrease in E. coli colonies was slower, and can be due to the inactivation by toxic factors present in the wastewater.…”
Section: Discussioncontrasting
confidence: 89%
“…Thus, terrestrial DOM via bacteria could be quite important to either zebra mussels or zooplankton. It is widely known that zooplankton can assimilate bacteria (Jansson et al 2007), and bacterial consumption by zebra mussels has been observed in the lab (Selegean et al 2001). That the zooplankton in the Hudson directly consume significant material of terrestrial origin would be consistent with laboratory studies that have shown that Daphnia can grow and reproduce on mixtures of terrestrial leaves and phytoplankton or on microbially colonized pollen grains alone (Brett et al 2009;Masclaux et al 2011).…”
Section: Discussionsupporting
confidence: 54%
“…and pathogenic protozoa (Cryptosporidium spp., Giardia duodenalis, and Acanthamoeba spp.). Data about protozoa bioaccumulation by zebra mussels have been reported (Graczyk et al 2001(Graczyk et al , 2004Palos Ladeiro et al 2014), but as far as we know, the accumulation of other bacteria apart from E. coli has not been studied (Selegean et al 2001).…”
Section: Introductionmentioning
confidence: 99%